Beloved - Morrison, Toni (A Plume book, 1987)
Beloved is a dense, complex novel that yields up its secrets one by one. As Morrison takes us deeper into Sethe's history and her memories, the horrifying circumstances of her baby's death start to make terrible sense. And as past meets present in the shape of a mysterious young woman about the same age as Sethe's daughter would have been, the narrative builds inexorably to its powerful, painful conclusion. Beloved may well be the defining novel of slavery in America, the one that all others will be measured by. --Alix Wilber --This text refers to an out of print or unavailable edition of this title.